Multilevel assessment of determinants of dental caries experience in Brazil - Antunes JLF, Peres MA, Mello TRC, Waldman EA. (Blackwell Synergy, 2006)
To examine contextual and individual determinants of dental caries experience, documenting levels of the disease in Brazil.